Granulocyte-Colony Stimulating Factor-Induced Neutrophil Recruitment Provides Opioid-Mediated Endogenous Anti-nociception in Female Mice With Oral Squamous Cell Carcinoma - Scheff, Nicole N.; Alemu, Robel G.; Klares, Richard; Wall, Ian M.; Yang, Stephen C.; Dolan, John C.; Schmidt, Brian L. (Frontiers in Molecular Neuroscience, 2019)
Oral cancer patients report severe function-induced pain; severity is greater in females. We hypothesize that a neutrophil-mediated endogenous analgesic mechanism is responsible for sex differences in nociception secondary to oral squamous cell carcinoma (SCC). Neutrophils isolated from the cancer-induced inflammatory microenvironment contain ß-endorphin protein and are identified by the Ly6G+ immune marker. We previously demonstrated that male mice with carcinogen-induced oral SCC exhibit less nociceptive behavior and a higher concentration of neutrophils in the cancer microenvironment compared to female mice with oral SCC. Oral cancer cells secrete granulocyte colony stimulating factor (G-CSF), a growth factor that recruits neutrophils from bone marrow to the cancer microenvironment. We found that recombinant G-CSF (rG-CSF, 5 µg/mouse, intraperitoneal) significantly increased circulating Ly6G+ neutrophils in the blood of male and female mice within 24 hours of administration. In an oral cancer supernatant mouse model, rG-CSF treatment increased cancer-recruited Ly6G+ neutrophil infiltration and abolished orofacial nociceptive behavior evoked in response to oral cancer supernatant in both mal¬e and female mice. Local naloxone treatment restored the cancer mediator-induced nociceptive behavior. We infer that rG-CSF-induced Ly6G+ neutrophils drive an endogenous analgesic mechanism. We then evaluated efficacy of chronic rG-CSF administration to attenuate oral cancer-induced nociception using a tongue xenograft cancer model with the HSC-3 human oral cancer cell line. Saline-treated male mice with HSC-3 tumors exhibited less oral cancer-induced nociceptive behavior and had more ß-endorphin protein in the cancer microenvironment than saline-treated female mice with HSC-3 tumors. Chronic rG-CSF treatment (2.5 µg/mouse, every 72 hours) increased the HSC-3 recruited Ly6G+ neutrophils, increased ß-endorphin protein content in the tongue and attenuated nociceptive behavior in female mice with HSC-3 tumors. From these data we conclude that neutrophil-mediated endogenous opioids warrant further investigation as a potential strategy for oral cancer pain treatment.